Fractional Electrodamage in A549 Human Lung Cancer Cells - Hilario Martines-Arano; Jose Alberto Arano-Martinez; Manuel Alejandro Mosso-Pani; Alejandra Valdivia-Flores; Martin Trejo-Valdez; Blanca Estela García-Pérez; Carlos Torres-Torres (Fractal and Fractional)
Fractional electrodamage in A549 human lung cancer cells was analyzed by introducing a non-integer order parameter to model the influence of electrical stimulation on cellular behavior. Numerical simulations were conducted to evaluate the conversion of electrical energy to heat within A549 cancer cells, emphasizing the electrocapacitive effects and electrical conductivity in modulating dielectric properties. Using the Riemann–Liouville fractional calculus framework, experimental results were accurately fitted, demonstrating the non-integer nature of electrodamage processes. The study identified a strong dependency of electrical behavior on frequency, revealing a critical role of fractional dynamics in the dielectric breakdown and susceptibility of A549 cells to voltage changes. These findings advance our understanding of cellular responses to electrical fields and provide insights into applications in cancer diagnostics, monitoring, and potential therapeutic treatments.